PRODUKSI GAS HASIL BIODEGRADASI MINYAK BUMI: KAJIAN AWAL APLIKASINYA DALAM MICROBIAL ENHANCED OIL RECOVERY (MEOR) (Makara Journal of Science, 2009)
Gas Production Generated from Crude Oil Biodegradation: Preliminary Study on its Aplication in Microbial Enhanced Oil Recovery (MEOR). The objective of this study is to observe the capacity of gas production generated from crude oil degradation by the isolated bacteria. The gas in the MEOR could increase pressure in the reservoir, decrease oil viscosity, increase oil permeability-due to the increase of the porosity and viscosity, and also increase oil volume due to the amount of dissolved gas. A research on gas analysis of oil degradation by 6 isolated bacteria has been conducted. The bacteria isolates including Bacillus badius (A), Bacillus circulans (B), Bacillus coagulans (C), Bacillus firmus (D), Pasteurella avium (E) and Streptobacillus moniliformis (F). The trial on gas production, gas analysis and oil degradation analysis, was carried out by using SMSS medium. The test of gas production was done by using microrespirometer at 40°C. The result shows that B, C, D, E produce more gas than A and F. Gas of CO2, O2, CO, N2, CH4, and H2 were analyzed by using GC. The results show that only three gases were detected by GC i.e. CO2, N2, and O2. The concentration of CO2 and N2 gas increased while the concentration of O2 decreased over an 8th day of observation. CO2 gas producted by mix culture was higher than by the pure culture. On the 8th day of incubation, the production of CO2 gas by mix culture was 4,0452% while pure culture C and D only produced 2,4543% and 2,8729%. The mix culture increase simple hydrocarbon by 12.03% and the formation of a complex hydrocarbon by 3.07%. The mix culture (C-D) generated the highest concentration of CO2 gas as well as a synergistic concortium that has ability to degrade crude oil.